Coupled solute effects enable anomalous high-temperature strength and stability in nanotwinned Al alloys. (November 2020) - Li, Qiang; Xie, Dongyue; Shang, Zhongxia; Sun, Xing; Cho, Jaehun; Zhang, Yifan; Xue, Sichuang; Wang, Haiyan; Wang, Jian; Zhang, Xinghang
Abstract: Nanoprecipitates or grain refinement can effectively enhance the mechanical strength of Al alloys, but the room-temperature strengths of precipitation hardened and nanocrystalline Al alloys often fall below 1 GPa. Furthermore, they are largely plagued by precipitous mechanical softening at elevated temperature below 300°C, mostly due to degraded microstructural stability. Here, we report a mechanism of coupled solute effect in nanotwinned Al-Fe-Ti alloys that enables stability of nanograins up to 400°C and an unprecedented high-temperature flow stress of ~ 1.7 GPa at 300°C. The supersaturated Fe solutes in Al act as effective grain refiner, forming superstrong solid solution alloys. More importantly, empirical evidence combined with first principle calculations indicate that the Ti solutes delay the agglomeration of Fe solutes, thereby remarkably extending the temperature window for the stability of nanograins in nanotwinned Al alloys. This study highlights the opportunity to design ultrastrong and stable nanostructured alloys for potential high temperature applications via a coupled solute effect. Graphical abstract: Image, graphical abstract